Crystallographic studies of two variants of Pseudomonas aeruginosa IMPDH with impaired allosteric regulation. (1st September 2015) - Labesse, Gilles; Alexandre, Thomas; Gelin, Muriel; Haouz, Ahmed; Munier‐Lehmann, Hélène
<x xml:space="preserve">Abstract</x> Inosine‐5′‐monophosphate dehydrogenases (IMPDHs), which are the rate‐limiting enzymes in guanosine‐nucleotide biosynthesis, are important therapeutic targets. Despite in‐depth functional and structural characterizations of various IMPDHs, the role of the Bateman domain containing two CBS motifs remains controversial. Their involvement in the allosteric regulation of Pseudomonas aeruginosa IMPDH by Mg‐ATP has recently been reported. To better understand the function of IMPDH and the importance of the CBS motifs, the structure of a variant devoid of these modules (ΔCBS) was solved at high resolution in the apo form and in complex with IMP. In addition, a single amino‐acid substitution variant, D199N, was also structurally characterized: the mutation corresponds to the autosomal dominant mutant D226N of human IMPDH1, which is responsible for the onset of the retinopathy adRP10. These new structures shed light onto the possible mechanism of regulation of the IMPDH enzymatic activity. In particular, three conserved loops seem to be key players in this regulation as they connect the tetramer–tetramer interface with the active site and show significant modification upon substrate binding.